Modern treatment for extremities border-line burns - S. V. Bogdanov; O. N. Afaunova (Инновационная медицина Кубани)
About 80 % patients with thermal injury, referred to the in-patient hospital department, demonstrates border-line and surface burns. Regarding the number of the suffered patients the most important point refers to the treatment term reduction due to its improved efficiency and we consider it to be more essential as it has positive impact on treatment quality.Objective. We try to define efficiency of early surgical treatment in patients with extremity burns in our proposed way of complex treatment for skin boundary burns in comparison with traditional "waiting" technique of maintaining boundary burns in patients who have been operated in later terms. The essence of this way is that during the first 2-7 days after receiving a boundary burn in the functional zones and zones inclined to scarring formation, we carry out necrectomy to the lower layers of derma and autoplasty, and on other boundary sites with burns we remove fibrous and necrotic pellicle within surface dermal layers to the level of a bleeding layer and on the processed burn area we place a wound covering.Material and Methods. We analyzed treatment results in 141 patients, age range 4 months to 65 years, which were treated in the Burn Department, SPHBI ‘SRI-ORCH ’№ 1. The main group included 63 patients (43 infants and 20 adults) treated operatively in early terms. The comparative group included 78 patients (44 infants and 33 adults), all of those were treated with wet-to-dry dressing application and prolonged autodermoplasty as long as we observed formation of granulating wounds.Conclusion. This way for border-line skin burns complex treatment which we have developed comparing to traditional treatment, improves treatment quality in patients, reduces treatment terms and increases its efficiency. During the postoperative period it allows to prevent scar development and to achieve positive esthetic results.